Binding of Soluble Yeast β-Glucan to Human Neutrophils and Monocytes is Complement-Dependent - Bose, Nandita; Chan, Anissa SH; Guerrero, Faimola; Maristany, Carolyn M.; Walsh, Richard M.; Ertelt, Katie E.; Jonas, Adria B.; Gorden, Keith B.; Dudney, Christine M.; Wurst, Lindsay R.; Danielson, Mike E.; Elmasry, Natalie; et al. (Frontiers in Immunology, 2013)
The immunomodulatory properties of yeast β-1,3/1,6 glucans are mediated through their ability to be recognized by human innate immune cells. While several studies have investigated binding of opsonized and unopsonized particulate β-glucans to human immune cells mainly via complement receptor 3 (CR3) or Dectin-1, few have focused on understanding the binding characteristics of soluble β-glucans. Using a well-characterized, pharmaceutical grade, soluble yeast β-glucan, this study evaluated and characterized the binding of soluble β-glucan to human neutrophils and monocytes. The results demonstrated that soluble β-glucan bound to both human neutrophils and monocytes in a concentration-dependent and receptor-specific manner. Antibodies blocking the CD11b and CD18 chains of CR3 significantly inhibited binding to both cell types, establishing CR3 as the key receptor recognizing the soluble β-glucan in these cells. Binding of soluble β-glucan to human neutrophils and monocytes required serum and was also dependent on incubation time and temperature, strongly suggesting that binding was complement-mediated. Indeed, binding was reduced in heat-inactivated serum, or in serum treated with methylamine or in serum reacted with the C3-specific inhibitor compstatin. Opsonization of soluble β-glucan was demonstrated by detection of iC3b, the complement opsonin on β-glucan-bound cells, as well as by the direct binding of iC3b to β-glucan in the absence of cells. Binding of β-glucan to cells was partially inhibited by blockade of the alternative pathway of complement, suggesting that the C3 activation amplification step mediated by this pathway also contributed to binding.